Are the mediolateral joint forces in the lower limbs different between scoliotic and healthy subjects during gait?. Issue 2 (December 2015) - Yazji, Mouna; Raison, Maxime; Aubin, Carl-Éric; Labelle, Hubert; Detrembleur, Christine; Mahaudens, Philippe; Mousny, Marilyne
Abstract Introduction The quantification of internal joint efforts could be essential in the development of rehabilitation tools for patients with musculo-skeletal pathologies, such as scoliosis. In this context, the aim of this study was to compare the hips joint mediolateral forces during gait, between healthy subjects and adolescents with left lumbar or thoracolumbar scoliosis (AIS), categorized by their Cobb angle (CA). Material and methods Twelve healthy subjects, 12 AIS with CA between 20° and 40° and 16 AIS in pre-operative condition (CA : > 40°) walked at 4 km/h on an instrumented treadmill. The experimental set-up include six infrared cameras allow the computation of the tridimensional (3D) angular displacement and strain gauges located under the motor-driven treadmill allow the computation of ground reaction forces (GRF). The hips joint mediolateral forces were calculated using a 3D inverse dynamic of human body. One-way ANOVA was performed for the maximum, the minimum and the range of medio-lateral forces at each joint of the lower limbs. When appropriate, a Tukey's post hoc was performed to determine the differences. Results The mediolateral forces were significantly lower at the right hip for AIS with CA between 20° and 40° compared to healthy subject. Conclusion The spinal deformation leads to a reduced medio-lateral force at the right hip, which could gradually change the scheme of postural adjustments for AIS during gait. Further research on the quantification of the joint lower limb efforts should include the knee and ankle joints to evaluate the impact of spinal deformation on the lower limb dynamic behaviour in AIS patients.